MANAJEMEN PENDIDIKAN ISLAM DALAM PENGEMBANGAN SEKOLAH/MADRASAH: manajemen pendidikan islam - Rudiansyah Gunawan (J-MD Jurnal Manajemen Dakwah, 2022)
Management of Islamic education in the development of schools/madrasahs plays an important role in an institution or educational institution, especially in schools/madrasas. In supporting the management, regulation, and operation of the system in an educational institution, educational management is needed. In Islam education management is very complete because it has been listed in the Al-Quran and Hadith. As stated by Hartani that education management is the art or science of managing educational resources to achieve the educational goals that have been set effectively and efficiently. Management of Islamic education is more specific and specific to Islamic educational institutions and also includes in general so that it is contained in the Qur'an with several verses indicating education management, especially Islamic education management. The education management contains functions that serve as a role, namely planning, organizing, mobilizing, monitoring, and evaluating. These are the main functions for both general education management and Islamic education management. Leadership in an educational institution is needed so that it can run according to the plans that have been formulated and can achieve the goals that have been set. There are several requirements that must be met to be a good leader and the skills or skills that must be possessed. One of them is to refer to the nature of the leadership of the Prophet Muhammad, which consists of Siddiq, Amanah, Tabligh, and Fatanah. The purpose of this writing is to contribute knowledge to education in order to develop schools/madrasahs through professional education management. some articles, but before being used, of course they are carefully studied to fit the topic of discussion used.